703 SARCOPENIA OBESITY AND MYOSTEATOSIS ARE RISK FACTORS FOR COMPLICATIONS FOLLOWING RESECTION OF OESOPHAGOGASTRIC CANCERS. (17th September 2021) - Siddaiah-subramanya, Manjunath; Kamarajah, Sivesh; Halle-Smith, Jame; Ghoneim, Abdulrahman; Sinha, Yashashwi
Abstract:  : Oesophagogastric cancer resection carries a morbidity, as high as 60%. Better patient selection, not only with regards to clinical stage but also with fitness reduces morbidity and improves outcome. Assessment of sarcopenia (SMI) and incremental shuttle walk test (ISWT) are two such tools to evaluate patients' fitness. We investigate the influence of these two tools in predicting post-operative outcomes following Oesophagogastric resection. Methods: All patients who underwent Oesophagogastric cancer resection between 2017–2019 and consented to participate in ISWT were included and outcomes evaluated retrospectively. Patient demographics, comorbidity profile and distance walked in ISWT were collected from the hospital cancer database. SMI was calculated on the pre-operative staging CT at the level of L3. Outcomes assessed included overall complications, major complications (Clavien-Dindo III-V) and 30-day mortality. Results: Sixty-seven patients (median age = 67) met the inclusion criteria with majority receiving neoadjuvant chemotherapy (79%). Overall complication rate was 69% including 34% major complications. There was no difference in overall and major complication between patients with ISWT distance of >350 and < 350 m. Sarcopenia was diagnosed in 58% of the patients. Adjusted analyses showed female patients (OR: 9.31, CI95%: 1.49–94.15, p = 0.030), myosteatosis (OR: 7.52, CI95%: 1.64–48.62, p = 0.017), and sarcopenic obesity (OR: 6.16, CI95%: 3.28–36.59, p = 0.021) to be independent predictors of overall complications. Correlation plot shows no interaction between SMI and ISWT scores. Conclusion: The study shows that ISWT does not predict post-operative mortality and morbidity following Oesophagogastric cancer resection. Sarcopenia is associated with higher overall complication rates. SMI and ISWT score do not correlate in predicting post-operative outcomes. We recommend that assessment of sarcopenia to be used routinely as a pre-operative assessment tool for prediction of outcomes in patients undergoing Oesophagogastric cancer resection.